The Transformation of Religious Habitus Among Mahasantri Through a Dormitory Program: A Sociological Analysis from Pierre Bourdieu’s Perspective - Riza Saputra; Syifa Qamari; Mutmainnah; Nor Amalia Husna (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The dormitory program serves as a strategic initiative aimed at cultivating students’ religious character through immersive communal living. Functioning beyond its role as a residential facility, the dormitory operates as a structured social field that facilitates the internalization of religious dispositions. This study adopts a descriptive qualitative methodology, drawing on in-depth interviews with alumni of the dormitory program and document analysis of the Ma’had al-Jāmi‘ah curriculum. Guided by Pierre Bourdieu’s theoretical framework—particularly the interrelated concepts of habitus, field, and capital—this research explores how religious practices, institutional oversight, and peer interactions within the dormitory environment contribute to the formation of a religious habitus among student-santri. The findings indicate that while the dormitory program significantly shapes students’ religious orientations, the durability of this habitus post-residency is contingent upon their access to cultural and social capital and the nature of the new social fields they enter. These results underscore the transformative potential of the dormitory program, while also highlighting the need for sustained strategies to support the continuity of religious values beyond the institutional setting.